Mechanistic advances and therapeutic applications of Zingiber officinale Roscoe - Pawan Kumar Verma; Bhawani Singh; Priyanka Sharma; Sheen Tukra; Abderrahmane Aït-Kaddour; Zuhaib F. Bhat (Food Chemistry Advances)
Ginger (Zingiber officinale Roscoe) is a plant with promising beneficial effects against various diseases and health disorders. Ginger-rhizome and its essential oils are used in traditional Chinese medicine and Ayurveda as herbal remedies for the treatment of various diseases such as cardiovascular, inflammatory, neurological, diabetic and nephrological disorders. It has been a part of food and beverages as a spice and appetizer in many cultures. The paper is focused on the pharmacological potential of rhizome and the impact of various isolated compounds on different body systems. The mechanisms responsible for the ethnomedicinal effects are discussed in detail along with recent advances in phytochemistry and phytopharmacology. Various pharmacological activities screened in our laboratory and relevant works of literature available on mechanistic studies have been included to maximize the therapeutic applications of different parts of the plant, especially the rhizome. The plant possesses potent anti-inflammatory, antioxidant, antimicrobial, and anticancer activities due to a wide array of phytochemicals such as gingerols, shogaols, paradols, and zingerones. The wide spectrum of activities of ginger-rhizome reinforces its long-standing use in traditional medicine and presents opportunities for further research in modern pharmacology.